Perbandingan Panjang Mooring Line Terhadap Karakteristik Pergerakan Kapal Fpso Menggunakan Analisa Numerik - Nadya Darwis (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
In analyzing moorings for FPSO (Floating Production Storage and Offloading), many things must be considered so that the mooring system can meet operability and safety standards. In this paper, we will discuss the stability of FPSO ships with varying mooring line lengths for FPSO ships with a capacity of 170218 DWT which will later be converted. The number of mooring ropes is limited to 4 with mooring rope lengths of 3100, 3200, 3300 m respectively. Variations in the length of the mooring line to clearly see the extent of the influence of changes in the length of the mooring line on the tension of each mooring line and the movement offset of the FPSO when moored and subjected to marine environmental loads (waves, wind, currents) using full dynamic analysis with the time method domain. From this study it can be seen that by increasing the length of the mooring line there will be a reduction in the maximum tension on the mooring line, but on the contrary there will be an increase in the offset of the ship's movement.